Pemanfaatan Alelopati Beberapa Jenis Gulma Sebagai Herbisida Nabati dan Dampaknya Terhadap Pertumbuhan dan Hasil Bawang Merah (Allium Ascalonicum L.) - Ikhsan Hasibuan; Prihanani Prihanani; Danner Sagala (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2008)
The investigation was done to use the allelopathical potency of tested weeds as botanical herbicide, to find the best concentration of weed extract, to find the effect of allelopathy to either weed of onion or the onion. The experiment was carried out in experimental land of Agriculture Faculty, The University of Hazairin, North Bengkulu and Laboratory of Agronomy for four months.The experiment was arranged factorially in a randomized block design with three replications. The kinds of extract weeds were Imperata cylindrica, Cyperus rotundus, Mikania micrantha and Ageratum conyzoides. Concentration was applied at 0%, 10%, 20%, 30%, and 40%.The result concluded that extract, concentration or interaction of the two not only affected insignificant to growth and yield of onion but also dry weight of weed. However, extract of Cyperus rotundus tent to suppress the weed around the onion. Concentration of extract showed inconsistent response to all parameters. It probably because the concentration was still low so that the effect of maintenance was dominant.